Comparison of neostigmine and sugammadex for hemodynamic parameters in cardiac patients undergoing noncardiac surgery - (:unkn) unknown (ELSEVIER SCIENCE INC, 2016)
Study Objective: The aim of this study is to compare the hemodynamic effects of neostigmine-atropine combination and sugammadex in patients with cardiac problems undergoing noncardiac surgery. Design: Prospective randomized study. Setting: In the operating room. Patients: Ninety patients with a class 2 or 3 cardiovascular disease according to the New York Heart Association classification and aged between 18 and 75 years undergoing noncardiac surgery were randomized. Interventions: Group N (n = 45) received 0.03 mg/kg IV neostigmine when T2 appeared as measured with a nerve muscle stimulator. When heart rate was 5 beats/min (+/- 10 beats/min) lower than the heart rate before administration of the medication, 0.5 mg IV atropine sulfate was given. Group S (n = 45) received 3 mg/kg IV sugammadex when T2 appeared as measured with a nerve muscle stimulator. Measurements: Heart rate, mean systolic and diastolic blood pressures, and electrocardiographic alterations including the QTc (QT Fredericia and QT Bazett) were recorded. Main Results: There were no significant differences between and within the groups in terms of QTc values. Sugammadex group had a significant decrease on heart rate 1 minute after the medication when compared to the measurement before the medication (P < .05). Heart rate and systolic blood pressure increased in neostigmine group 3 minutes after the medication and during postoperative measurements (P < .05). Sugammadex group had lower systolic, diastolic, and mean blood pressures and heart rate when compared to neostigmine group (P < .05). Conclusions: We suggest that sugammadex might be preferred as it provides more hemodynamic stability compared to neostigmine-atropine combination to reverse rocuronium-induced neuromuscular blockage in cardiac patients undergoing noncardiac surgery. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Sugammadex; Neostigmine; Atropine; Cardiac patient; Gamma-cyclodextrin; Rocuronium; INDUCED NEUROMUSCULAR BLOCKADE; REVERSAL; ROCURONIUM; ANESTHESIA; VECURONIUM; ATROPINE; QTC